PENGARUH KINERJA INTELLECTUAL CAPITAL TERHADAP KINERJA INTELLECTUAL CAPITAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Windri, Windri; Januarti, Indira (JURNAL AKUNTANSI DAN AUDITING, 2010)
The aims of this study are to analyze the effect of intellectual capital performance on intellectualcapital disclosure in annual report of manufacturing company listed in Indonesia Stock Exchange(IDX) period 2004-2006 and to analyze the level of intellectual capital disclosure in annualreport period 2004-2006. 50 companies was taken as samples in the research.This paper usescontent analysis to compile a measure of disclosure on each annual report of manufacturingcompany and statistical analysis to test whether intellectual capital performance has a positiveeffect to intellectual capital disclosure. Based on statistical analysis, it is concluded that theintellectual capital performance and firm size have a positive effect to intellectual capitaldisclosure. Leverage has no effect to intellectual capital disclosure. The result of content analysisshows that the intellectual capital disclosure in annual report of manufacturing company period2004-2006 are less than 50%.